AGN outflow shocks on Bonnor-Ebert spheres - Dugan, Zachary; Gaibler, Volker (The astrophysical journal, 2017)
Feedback from active galactic nuclei (AGNs) and subsequent jet cocoons and outflow bubbles can have a significant impact on star formation in the host galaxy. To investigate feedback physics on small scales, we perform hydrodynamic simulations of realistically fast AGN winds striking Bonnor-Ebert spheres and examine gravitational collapse and ablation. We test AGN wind velocities ranging from 300 to 3000 km s −1 and wind densities ranging from 0.5 to 10 m p cm −3 . We include heating and cooling of low- and high-temperature gas, self-gravity, and spatially correlated perturbations in the shock, with a maximum resolution of 0.01 pc. We find that the ram pressure is the most important factor that determines the fate of the cloud. High ram pressure winds increase fragmentation and decrease the star formation rate, but they also cause star formation to occur on a much shorter timescale and with increased velocities of the newly formed stars. We find a threshold ram pressure of ∼2 × 10 −8 dyn cm −2 above which stars are not formed because the resulting clumps have internal velocities large enough to prevent collapse. Our results indicate that simultaneous positive and negative feedback will be possible in a single galaxy, as AGN wind parameters will vary with location within a galaxy.
Gesehen am 23.10.2017